Media Framing of Disasters and Its Implications for Tourism Industry Policy: Case of Surabaya terrorist attack 2018 and Mt. Agung eruption 2017, Indonesia - Erda Rindrasih (Jurnal Humaniora, 2022)
Tourist destinations worldwide are periodically jeopardised by natural disaster events that threaten tourists’ safety; consequently, the tourism industry is impacted. Mass media has a role to communicate and warn the public about disaster. Media portrayal on disaster events is likely to contribute to the tourism industry recovery and resilience. However, media has played a role in sending a negative message to tourists, making them hesitate to visit the destination. Limited researches have focused on how the media frames disaster events, and how policy makers could intervene. Based on analysis of media coverage of the Surabaya terrorist attack in 2018 and Mt. Agung eruption in 2017, this paper looked at how media framed disaster events and its consequences to the tourism industry policy. A content analysis of mass media from both national and international newspapers of Australia, Malaysia, and Singapore were conducted. The research identified five different framings on the two disasters, including source of problems, impact, solution, responsibility, and adaptive versus maladaptive. Findings also highlights the limited policy response towards these potentially negative media portrayal. Based on these findings, partnership between media and the government should be fostered to encourage post-disaster recovery.